2011
DOI: 10.1111/j.1365-2583.2011.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of five CYP4 genes from Asian citrus psyllid and their expression levels in Candidatus Liberibacter asiaticus‐infected and uninfected psyllids

Abstract: Previously, we reported that Candidatus Liberibacter asiaticus (Las)-infected Diaphorina citri are characterized by lower levels of cytochrome P450 monooxygenases than uninfected counterparts. In the present study, we investigated expression levels of family 4 cytochrome P450 (CYP4) genes in Las-infected and uninfected D.citri adults. Five novel CYP4 genes (CYP4C67, CYP4DA1, CYP4C68, CYP4DB1 and CYP4G70) were identified. Four of the five CYP4 genes were expressed at significantly higher levels in uninfected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 52 publications
3
74
0
1
Order By: Relevance
“…The effects of CLas infection on psyllid genes, including ATP synthase ␣-and ␤-subunits mitochondrion-like (ATP synthase A and B), V-type proton ATPase catalytic subunit A (V-ATPase-V1a), the transitional endoplasmic reticulum ATPase (TER94), nucleotide diphosphate kinase (NDPK), and AMP-activated protein kinase ␣-subunit (AMPK-A) genes in D. citri adults, were evaluated using RT-qPCR as described by El-Shesheny et al (23). The actin gene was used as a reference (endogenous gene) for comparing the relative levels of gene expression among treatments (46). Table 3 contains the primers used for gene expression.…”
Section: Diaphorina Citri Coloniesmentioning
confidence: 99%
“…The effects of CLas infection on psyllid genes, including ATP synthase ␣-and ␤-subunits mitochondrion-like (ATP synthase A and B), V-type proton ATPase catalytic subunit A (V-ATPase-V1a), the transitional endoplasmic reticulum ATPase (TER94), nucleotide diphosphate kinase (NDPK), and AMP-activated protein kinase ␣-subunit (AMPK-A) genes in D. citri adults, were evaluated using RT-qPCR as described by El-Shesheny et al (23). The actin gene was used as a reference (endogenous gene) for comparing the relative levels of gene expression among treatments (46). Table 3 contains the primers used for gene expression.…”
Section: Diaphorina Citri Coloniesmentioning
confidence: 99%
“…Data generated thus far suggest that cross-resistance is not likely between these 2 insecticides based on known mechanisms of resistance (Nauen et al 2013(Nauen et al , 2015. It remains to be demonstrated experimentally, but given the difference in chemical structure, it is unlikely the CYP4 P450 monooxygenases associated with imidacloprid exposure in D. citri will also be responsive to flupyradifurone (Tiwari et al 2011b;Killiny et al 2014). Interestingly, the RR50 estimates for flupyradifurone clustered with those of imidacloprid and thiamethoxam, except in 2 cases where thiamethoxam was higher and the RR50 estimate for flupyradifurone remained similar to that observed for imidacloprid (Fig.…”
Section: Flupyradifuronementioning
confidence: 87%
“…In 2010, the problem increased, with decreased susceptibility to the majority of insecticides used to manage D. citri throughout Florida (Tiwari et al 2011a). Subsequent molecular investigations demonstrated the induction of a suite of CYP4 genes in adult psyllids in response to contact exposure with imidacloprid (Tiwari et al 2011b). CYP genes code for a major class of enzymes (cytochrome P450 monooxygenases) frequently associated with insecticide resistance in insects (Li et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Decreases in GST and P450 activities have been reported in cases of bacterial infection, but not in cases of virus. 36,37) The Asian citrus psyllid, Diaphorina citri, infected with the Gramnegative bacteria Candidatus Liberibacter asiaticus (Las) shows significantly lower activity as compared to uninfected ones, suggesting that the defense response against the xenobiotic may be suppressed by the invading virus. Although there have been no reports that direct virus infection induced high activity of detoxification enzymes, it is reported that the p450 and GST of the detoxification enzyme increased in parasitized hosts with infection by a symbiotic virus, which is injected into the host hemocoel with the eggs of an endoparasitoid, Vestalis (=Cotesia) plutellae-Plutella xylostella, host system.…”
Section: Discussionmentioning
confidence: 99%